Effect of furcellaran incorporation on gel properties of sardine surimi - Tanyamon Petcharat; Manat Chaijan; Supatra Karnjanapratum (International Journal of Food Science & Technology, 2021)
Abstract Effects of furcellaran, powder (FURP) and solution (FURS), incorporation (2‐8% based on surimi solid content) on gel properties of sardine ( Sardinella albella ) surimi were investigated. Breaking force, hardness, gumminess, chewiness, and whiteness of gels increased with increasing FURP or FURS contents ( P < 0.05), where the highest values were observed in gel containing 8% FURS ( P < 0.05). Expressible moisture content of gel decreased as levels of furcellaran increased ( P < 0.05). The gel deformation, springiness, and cohesiveness were not affected by furcellaran ( P > 0.05) as well as the polymerization of myosin heavy chain as visualised by SDS‐PAGE. FURP and FURS could enhance the interconnection between chains during heating as indicated by the higher G′. Addition of furcellaran, especially FURS, up to 6% increased sensory property of resulting gel ( P < 0.05). Anywise, an abatement in overall likeness score was found in gel with 8% FURS. Finer and denser microstructural network was observed in gel containing 6% FURS when compared to control. Therefore, furcellaran, prepared as solution, at an appropriate level can improve the overall quality of sardine surimi.
Keywords: Meat and Animal Product Quality; Neurobiology and Insect Physiology Research; Animal Nutrition and Physiology